Consumer culture and society - Wiedenhoft Murphy, Wendy A. (SAGE, 2017)
"Consumer Culture and Society offers an introduction to the study of consumerism and mass consumption from a sociological perspective. It examines what we buy, how and where we consume, the meanings attached to the things we purchase, and the social forces that enable and constrain consumer behavior. Opening chapters provide a theoretical overview and history of consumer society and featured case studies look at mass consumption in familiar contexts, such as tourism, food, and higher education. The book explores ethical and political concerns, including consumer activism, indebtedness, alternative forms of consumption, and dilemmas surrounding the globalization of consumer culture"--Provided by publisher.